A tessitura de Colasanti: viés feminino, fios simbólicos e teias intertextuais - Telini, Érika Alves de Moraes (2021)
Marina Colasanti is a writer who stands out in contemporary literature for the high symbolic and poetic content used in the construction of her stories. Although she presents a pluri significant literary creation, her work is still little considered by critics and rarely seen in the academic field, which made her the object of study of this essay. In that way, to reveal these substantial aspects in the writer's production, three short stories will be analyzed in this paper – A moça tecelã, Além do bastidor e Fio após fio – part of Mais de 100 histórias maravilhosas, which have in common the use of the needlework metaphor and the subversion of traditional fairy tales in the post-modern context, details that are unveiled in the shadow of the marvelous, a key piece to finish off the questions made. Considering that there is an intense intertextual movement of rereading in contemporaneity, the literary corpus of this study, when examining Colasanti's narrative texture, requires the archetypal image of the weaver, reproduced in such a significant way in literature, to unravel the threads that lead to the author's writing: the female role addressed in its plot and the symbolic and intertextual threads conveyed by the marvelous in the analyzed narratives. KEYWORDS: Colasanti. Fairy tale. Feminine. Intertextuality. Textures.